MODEL OF INVESTMENT OPTIMIZATION IN INDUSTRIAL ENTERPRISES PRODUCTION INFRASTRUCTURE - Danyliuk, M. O.; Kravchuk, M. M.; Bilan, V. M. (Scientific Bulletin of Ivano-Frankivsk National Technical University of Oil and Gas (Series: Economics and Management in the Oil and Gas Industry), 2018)
The article deals with the process of optimization of investment sources and their distribution among the spheres of the furniture enterprises industrial infrastructure. Possible variants of quantitative estimation of efficiency of investment resources distribution into industrial infrastructure by spheres are analyzed. It is determined that optimization of industrial infrastructure areas financing involves the development of a scientifically grounded method of financial resources distribution, which provide the maximum economic effect of their implementation, both in terms of objects and periods, in the conditions of available volumes of own and borrowed resources. The maximum gross profit is used as the criterion of optimality when drawing up investment plans. The proposed economic-mathematical model of investments optimization in the furniture enterprises production infrastructure, in comparison with the existing ones, allows the optimal distribution of own and borrowed financial resources between particular spheres and periods, which adequately maximizes the economic effect.